Evolución de las temperaturas medias de la estación cálida (abril-septiembre) en la mitad del norte de España durante la Pequeña Edad del Hielo (siglos XVI al XIX) - Saz Sánchez, Miguel Ángel (Geographicalia, 2015)
In this work, we present the dendroclimatic reconstruction of the mean temperatures of the warm season (april to September) during the Little Ice Age (LIA) in eight weather stations located in different climatic conditions in the north half of Spain. The most important cold phases appears in 16th century, during the three first decades and in the 50’s, 60’s and 70’s. Temperatures are warmer in 17th and 18th centuries, with a new cold phase in the 19th century.These cold episodes agree with others of the same sign and chronology identified in other European regions, although in the north half of Spain we have not identified important cold phases in the 17th century, period in which hemispheric mean temperature series indicate the coldest phases into LIA.